2011
DOI: 10.1007/s10008-011-1579-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pretreatment of polycrystalline gold with OH• radicals on the electrochemical nucleation and growth of platinum

Abstract: The nucleation and growth of platinum on polycrystalline gold was studied by chronoamperometry, cyclic voltammetry, and atomic force microscopy before and after treatment of the gold surface with hydroxyl (OH • ) radicals. Two different procedures of mechanical polishing of the gold surface ("coarse polish" and "fine polish") were applied before the treatment with OH • radicals. The nucleation and growth of Pt was much better reproducible on electrodes which underwent a "coarse polish". The treatment of the Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…• radicals resulted in a reduction in the number of active sites for Pt nucleation [29]. Prior to this work, Kolb investigated the cyclic voltametric behaviour of single crystal gold surfaces where it was found that there was a significant peak prior to the monolayer oxide formation process that could be attributed to the level of surface defects which were step edges on Au(111) electrodes [30,31].…”
Section: Resultsmentioning
confidence: 99%
“…• radicals resulted in a reduction in the number of active sites for Pt nucleation [29]. Prior to this work, Kolb investigated the cyclic voltametric behaviour of single crystal gold surfaces where it was found that there was a significant peak prior to the monolayer oxide formation process that could be attributed to the level of surface defects which were step edges on Au(111) electrodes [30,31].…”
Section: Resultsmentioning
confidence: 99%
“…Also other aspects, as for instance a possible effect of formation of hydroxyl radicals initiating and/or accelerating gold dissolution should be included. [69][70][71][72] Nevertheless, the proposed models can capture all the experimentally observed aspects of gold dissolution described in this work. In summary, the local de-passivation of the surface during oxide formation/reduction as well as oxygen evolution is determining transient and steady-state dissolution of gold, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…may be responsible. Here, a comparison of the present results with those of our earlier electrochemical studies is very interesting: in previous studies, we have shown that at poly-crystalline gold, OH · radicals (1) preferably knock out active sites of electrocatalytic reactions (oxygen and hydroquinone reduction), and (2) they also knock-out the active sites for platinum deposition [1][2][3]. Hence, there is the possibility that the active sites for electrocatalysis and electrodeposition may be non-Au{111} faces, i.e., grain boundaries or locations with high defect concentrations.…”
Section: Discussionmentioning
confidence: 63%
“…Previously, we have reported on the interaction of OH · radicals with the surface of poly-crystalline noble metals (Au, Pt, Pd, and Ag) [1][2][3] and glassy carbon [4]. Particular attention was given to alterations of the surface morphology, the electrocatalytic properties, and the properties of the surfaces in nucleation growth of metal deposition [1,5].…”
Section: Introductionmentioning
confidence: 98%